“Buying a Pig in a Poke”: The Problem of Elasmobranch Meat Consumption in Southern Brazil - Bornatowski, Hugo; Braga, Raul Rennó; Kalinowski, Carolina; Vitule, Jean Ricardo Simões (Ethnobiology Letters, 2015)
In Brazil, the demand for sustainably certified seafood is increasing and retailers have promised to source all seafood from sustainable sources by 2015. In the southern portion of the country, elasmobranch meat is sold as cação, and consumers are often unaware that cação refers to any type of elasmobranch. The present study used questionnaires to investigate the lay public’s knowledge of elasmobranch meat sold in a Brazilian city. Shoppers were surveyed at supermarkets in Curitiba, the largest city in southern Brazil. The study revealed that people do not link commercialized cação meat to sharks and rays (Elasmobranchii), with more than half of respondents who claimed to have already eaten cação did not think they had ever eaten shark or ray. The educational profile of interviewees suggests that this lack of knowledge may be even more common in other segments of Brazilian society. Therefore, we suggest that ecological information about elasmobranchs should be included in Brazilian elementary and high school curricula. Such a measure has the potential to modify behavior, create awareness, and stimulate responsibility throughout society, with the primary goal of reducing shark meat consumption and, ultimately, guaranteeing the long term conservation of marine resources.